From Campus to Career: The Influence of Soft Skills on Employability - Elkhayma, Rachid; Ezzaidi, Mohamed (Journal of Digital Sociohumanities, 2025)
World economies have become more globalized and interconnected, with new advanced aspects of employment that are highly automated and technological. This leads to new work requirements that have rapidly been evolving since the beginning of the twenty-first century. Performing in such a competitive environment necessitates qualified job candidates who are not only competent in hard knowledge but also in soft skills. This forces employers to look for graduates with strong interpersonal and problem-solving skills, and a significant ability to manage various tasks and missions. In this context, this paper investigates the status of soft skills, students’ and employers’ attitudes towards them, and the possible merit and / or insignificance attributed to these skills for the student’s current educational and later professional endeavor. 120 Engineering and Science students from Hassan II and Cadi Ayyad Universities and 15 Casablanca and Rabat-based companies participated in the study. The findings reveal that both students and employers give greater importance to soft skills as essential requirements for job finding and employment success.